ANALYSIS OF MATHEMATIC REPRESENTATION ABILITY BY USING YOUTUBE MEDIA AS A MATHEMATICS LEARNING SOURCE - Rahmah, Kamilia; In’am, Akhsanul; Laila, Alfi Rachma Nisfi (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2022)
The purpose of this study was to describe the ability of mathematical representation by utilizing YouTube as a source of learning mathematics. The type of research used is descriptive qualitative research. The research subjects were 3 students of class VIII SMPN 1 Bluto who were chosen as research subjects by considering the similarity of mathematical abilities and the results of recommendations from the teacher. Data collection techniques and instruments in this study were tests of mathematical representation abilities and interviews. The data analysis in this study is reduction in the form of processed mathematical representation ability test data, data presentation in the form of mathematical representation ability test data results, and conclusions to describe students' representation abilities using learning resources in the form of youtube and linked to the results of interviews. The results showed that the high-ability representation ability met the three indicators, namely verbal representation, mathematical expression, and visuals. Students who have moderate ability meet the two indicators of mathematical representation ability, namely verbal representation, mathematical expression, but visual representation has not been able to describe. Students with low ability meet one indicator of mathematical representation ability, namely an indicator of mathematical representation ability, namely verbal representation